Study of pattern of congenital anomalies at tertiary center in Maharashtra, India - Yadav, B. B.; Yadav, S. B.; Damase, P. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To highlight common pattern of congenital malformation seen at hospital population of tertiary care center in Maharashtra. Methods: The study was a descriptive prospective study and conducted in the department of obstetrics and gynaecology of government medical college Latur, Maharashtra for a period of six months. Study includes all womens coming for 2nd trimester MTP due to congenital anomalies in foetus and women’s admitted in labour having anomalous foetus. Details of maternal age, parity, type of anomaly present and sex of fetus were noted. Results: Total babies born in the study period were 3482 (including the second trimester abortions). Total babies with congenital abnormality were 75, making the prevalence 2.15%. 10 cases (13.33) had multiple anomalies involving more than one system. The predominant system involved was central nervous system 40 (53.33%) followed by gastrointestinal system 15 (20%). In this study male babies affected more than females. Conclusions: Prevalence of the congenital anomalies will be definitely higher at tertiary care center and to know prevalence in community, more community based studies are required. Increased awareness about preventable risk factors may help in reducing the incidence of congenital anomalies.